Pembuktian Harta Bersama Dalam Perceraian Perkawinan Campuran Tanpa Perjanjian Kawin di Indonesia - Dwisana, I Made Arya; Resen, Made Gde Subha Karma (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 6 No 03 (2021), 2021)
Abstract The purpose of this research is to to find out and examine the position of Shared Property and the system of proof of joint property in the divorce of mixed marriage without marriage agreement This research uses normative legal methods and uses the approach of Legislation (The Statue Approach) and the approach of fact (The Fact Approach). The position of joint property in mixed marriage based on the Law in Indonesia is stipulated in Article 35 paragraph (1) of the Marriage Law stipulated that "the property obtained during the marriage is to be a joint property". The system of proof of joint property in a mixed marriage divorce without a marriage agreement is the person who sues the property together in case of divorce, he must prove that the property is a joint property. although the law does not govern the proof of joint property but the judge can decide the case based on his conviction (The Rechtsvinding School).   Abstrak Tujuan penelitian ini yaitu untuk mengetahui dan memahami Kedudukan Harta bersama serta sistem pembuktian harta bersama dalam perceraian perkawinan campuran tanpa perjanjian kawin Penelitian ini menggunakan metode hukum normatif serta menggunakan pendekatan Perundang-Undangan (The Statue Approach) dan pendekatan fakta (The Fact Approach). Kedudukan Harta bersama dalam Perkawinan campuran berdasarkan Hukum di Indonesia diatur dalam Pasal 35 ayat (1) UU Perkawinan menentukan bahwa “harta benda yang di peroleh selama perkawian adalah menjadi harta bersama”. Sistem pembuktian harta bersama dalam perceraian perkawinan campuran tanpa perjanjian kawin yaitu orang yang menggugat harta bersama apabila terjadi percerian maka ia harus membuktikan bahwa harta tersebut merupakan harta bersama. meskipun undang-undang tidak mengatur mengenai pembuktian harta bersama tetapi hakim dapat memutuskan perkara berdasarkan keyakinannya (Aliran Rechtsvinding).